Improving Methods For Calculating Profitability And Its Analysis - Ismaylov Kuatbay Sarsenbaevich (Genius Journals, 2025)
In a scientific article, using profitability methods, the level of profitability of business entities is calculated. As a result of the analysis of the level of profitability of the subjects, proposals and recommendations were developed to increase the level of profitability
Keywords: profitability; net profit; sales revenue